STRATEGIC COMMUNICATIONS – THEORY AND DEVELOPMENT - Pavić, Aleksandar; Hatidza, Berisa Alil (National interest, 2025)
Strategic communications are one of the key instruments of national security strategy, enabling states to manage the information space, shape the perception of security threats, and support the realization of national interests. Although the concept of strategic communications is relatively new, its application dates back to the earliest forms of military and diplomatic strategy, and today it has become an essential element of international relations and security policy. The development of technology, especially artifcial intelligence, has signifcantly improved strategic communications, enabling automated analysis, personalized information distribution, and proactive crisis management. This paper explores the place and role of strategic communications in national security through the prism of realist, liberal, and constructivist theories of international relations. The aim of the research is, on the one hand, to determine how modern technologies, primarily artifcial intelligence, are changing the scope and character of strategic communication, and on the other hand, to analyze how theoretical models can serve as a basis for the design and implementation of communication strategies in the context of national security. The paper starts from the hypothesis that effective strategic communication requires an integral approach that connects technological tools, institutional practice, and scientifc reﬂection. By applying content analysis and the hypothetical–deductive method, the paper also considers specifc case studies on the conﬂicts in Ukraine, Syria, and Israel, in which strategic communications play a key role in shaping public perception, delegitimizing opponents, and mobilizing support. The research confrms that integrating artifcial intelligence into strategic communications signifcantly improves the ability of states to protect their interests and act in a complex international community. The scientifc contribution of the work is reﬂected in the theoretical articulation of strategic communications as a structural component of national security strategy, but also in the recognition of their transformative potential in the digital era. It is concluded that strategic communications have become an indispensable mechanism of national and foreign policy, whose scientifc and technological foundation is the basis of modern security strategies.
Keywords: strategic communications; artificial intelligence; national security strategy; realism; liberalism; constructivism